Humanities Laboratory as Critical Paideia: Aesthetic Journey Confronting the Notion of Perfectibility as a Humanizing Dynamics in Health - Izumi Sakamoto, Jacqueline (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
This study is part of the FAPESP Regular Research Project “The pathologies of modernity and the remedies from humanities: investigation and experimentation”, and it intends to discuss, at the confluence of research and experimentation, to what extent dehumanization can be seen as a “pathological symptom” of Modernity, when following an Anthropology of Human Perfectibility as its basis. This work also intends to discuss to what extent the experience of Humanities can be presented as a “remedy” or a humanization journey (critical “Paideia”) within the health scope.